2015
DOI: 10.3109/15569527.2015.1004079
|View full text |Cite
|
Sign up to set email alerts
|

Peripapillary choroidal thickness in patients with chronic obstructive pulmonary disease

Abstract: Hypoxia in COPD seems to affect the choroidal thickness. Thinning of the choroid may be attributed to increased vascular resistance and reduced blood flow in patients with COPD. The possible effects of the disease to the eye may be clarified through the role of the choroidal vasculature in the blood supply of the anterior optic nerve head.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 28 publications
1
50
2
Order By: Relevance
“…Whilst better segmentation algorithms are already available to overcome the current limitations, the biggest challenge is that choroidal thinning undergoes significant diurnal fluctuations (Kinoshita et al, 2016) and its thinning is seen in many other conditions, including aging (Barteselli et al, 2012), myopia (Ho et al, 2013), uveitis (Baltmr et al, 2014), chronic obstructive pulmonary disease (Ozcimen et al, 2016). It also has limited application in the detection of age-related macular degeneration (Pilotto et al, 2015; Yiu et al, 2015) and glaucoma (Li et al, 2015; Toprak et al, 2016).…”
Section: Retinal Biomarkersmentioning
confidence: 99%
“…Whilst better segmentation algorithms are already available to overcome the current limitations, the biggest challenge is that choroidal thinning undergoes significant diurnal fluctuations (Kinoshita et al, 2016) and its thinning is seen in many other conditions, including aging (Barteselli et al, 2012), myopia (Ho et al, 2013), uveitis (Baltmr et al, 2014), chronic obstructive pulmonary disease (Ozcimen et al, 2016). It also has limited application in the detection of age-related macular degeneration (Pilotto et al, 2015; Yiu et al, 2015) and glaucoma (Li et al, 2015; Toprak et al, 2016).…”
Section: Retinal Biomarkersmentioning
confidence: 99%
“…Spectral Domain‐Optical coherence tomography (SD‐OCT) is an easily applied, non‐invasive and non‐contact imaging modality obtaining detailed in vivo assessment of retina and choroid . It has recently gained an important role in the diagnosis and follow‐up of retinal diseases and ocular involvements of neurodegenerative disorders . Near‐infrared light is used in OCT to analyse the integrity of ganglion cells [the ganglion cell layer (GCL)] and the axons [the retinal nerve fibre layer (RNFL)] in the optic nerve.…”
Section: Introductionmentioning
confidence: 99%
“…Ozcimen et al. ) demonstrated that the peripapillary choroid in the inferior segments of patients with COPD was significantly thinner than other peripapillary choroid segments and also thinner than those of control patients. In COPD, choroidal thinning might be due to hypoxia and vascular endothelial dysfunction, making the choroid more susceptible to retinal and choroidal diseases (Ozcimen et al.…”
Section: Methodsmentioning
confidence: 97%
“…Three studies evaluated the peripapillary choroidal thickness of patients with COPD (Table ) (Ozcimen et al. ; Ugurlu et al. ; Gok et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation